Fenomén biologická půdní krusta v aridních oblastech - Řeháková, K. (Klára); Čapková, K. (Kateřina) (2017)
Biological soil crusts are communities of organisms, which occur throughout the world, on all continents, mainly in cold and hot arid areas. In arid areas they create an important part of ecosystems and their coverage can reach up to 70 %. To a lesser extent it is possible to find them in other biotopes such as open Mediterranean forests, on the exposed soils of alpine and tundra vegetation or in steppes and on the soils of mining areas. in this article, we focuse on the communities from arid environment. Biological soil crusts influence the physical and chemical soil characteristics in deserts, and thus improve environmental conditions for vascular plants, animals and humans. These fragile ecosystems could easily be destroyed and their recovery at the original habitat could last for half a century.